Analisis Kualitas Pelayanan Administrasi Status Perkawinan Belum Tercatat Melalui Program Kalimasada di Kelurahan Rungkut Menanggal Kota Surabaya - Risma Adelia; Trenda Aktiva Oktariyanda; Meirinawati M; Deby Febriyan Eprilianto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to design a website as a marketing medium for certified coffee seedlings to expand market reach, enhance customer trust, and simplify the ordering process. The method used is Research and Development (RD), which includes needs analysis, system design, implementation, and testing. The results show that the website is able to present product information, certification, prices, stock, and online ordering, thereby supporting the improvement of promotional effectiveness and customer service.